2009
DOI: 10.1159/000257525
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy: The Lebanese Experience

Abstract: Background: Endoscopic third ventriculostomy (ETV) has gained wide popularity as a first-line treatment for obstructive hydrocephalus (OHC). We have been performing ETV since 1998. We report our experience with this technique in the management of OHC. Methods: Between 1998 and 2007, we performed 49 ETV procedures in 46 patients suffering from OHC. Medical records were retrospectively reviewed. Success was defined as shunt-free survival. Results: There were 29 males and 17 females with a mean age of 23 years (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 104 publications
2
6
0
Order By: Relevance
“…The overall SR to restore CSF circulation was 80% and the absolute CR was 13%. These data are in accordance with those reported in the literature [28,29,30,31,32]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The overall SR to restore CSF circulation was 80% and the absolute CR was 13%. These data are in accordance with those reported in the literature [28,29,30,31,32]. …”
Section: Discussionsupporting
confidence: 93%
“…Current experience throughout the world shows that this treatment is a good alternative to the use of shunts in many cases of brain disease, and particularly in obstructive hydrocephalus. ETV is considered to be a simple, fast and safe procedure in children [13,18,19,26,27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…populations [11][12][13][14][15] or combined pediatric and adult populations. [16][17][18][19][20][21] Studies evaluating the utility of ETV in the treatment of all causes of adult hydrocephalus are less frequent. 22,23 This report reviews the experience with 250 ETV procedures performed by a single neurosurgical service over a 14.5-year period for the management of a variety of conditions causing hydrocephalus in adults.…”
mentioning
confidence: 99%
“…[14] Most studies both in developing and developed nations had reported an ETV success within the range of 70-80%. [15][16][17][18] The standard imaging modality for diagnosis and classification of hydrocephalus is a brain CT scan. Use of MRI does not add any advantage but rather more expensive.…”
Section: Discussionmentioning
confidence: 99%